Perjanjian Kerjasama Antara Pengusaha BesiDengan Investor Studi Kasus tentang Sengketa pada Perusahaan Dhemes di Sukoharjo - Pratama, Sandhy Cahya; , Shalman Al-Farizy, S.H; , Darsono, S.H., M.Hum (2016)
This study aims to determine the agreement made between the entrepreneur iron with investors already running cooperation and to determine how these businessmen to return capital to investors who have invested in the business and would be reclaimed by the investor. The research method using empirical juridical approach to the descriptive nature of the research. Data sources include primary data, interviews and secondary data sources include primary and secondary law. Data were collected by literature study and interviews. Data were analyzed using qualitative analysis. The results showed that the agreement made between the entrepreneur iron with investors already running cooperation by way of investing in Companies Dhemes not comply with the provisions of Article 1320 Penal Code regarding the terms validity of the agreement, in which investors are only focused on the promise will get every month is Rp 25,000.000, - with not too concerned about risks as well as the not so thorough and meticulous about the importance of a legal agreement. While the return on capital that has been invested by the investor, the entrepreneur is not able to return capital to investors with cash, but paid in installments or installments for one month until paid.